(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2019)
Jatropha curcas L. belongs to family Euphorbiaceae, Jatropha curcas is a valuable multi-purpose crop, historically it was used as medicine for wounds and leaves used as drinks against malaria, jatropha plants used to control soil degradation, alleviate erosion, desertification and increase soil fertility, however, in last decades there is more attention to use jatropha oil for produce biodiesel, Jatropha curcas is easily propagated by seeds or stem cutting, it is tolerant for drought for longtime, it is grow well with treated wastewater, also, it can be grown on marginal land. Jatropha curcas seed have about 32-40% valuable oil used to produce biofuel, therefore, it could be the source for biodiesel production particularly in arid and semiarid regions.